S.B Pharmacy Sdn. Bhd / Norhidayah Azmy ... [et.al]. - Azmy, Norhidayah; Samian, Naim Natasya; Ab. Moin, Zuraidah; Ismail, Noorizlin; Mohamad, Marlinah (Faculty of Civil Engineering, 2001)
S.B Pharmacy Sdn. Bhd. is the combination of five young potential entrepreneurs of UiTM Shah Alam, Selangor graduates. After a few discussions all the members agreed to set up a pharmacy. The type of our business is Sendirian Berhad ( Private Limited ) because of the advantages for the shareholders and the benefit to the company. The factors that attracted us to choose Sdn. Bhd. are because the financial source is easy to obtain from the changer of the share property or form the loan of the financial institution. The private asset of the shareholders is not in the company dependent. One more the advantages of this type is all the shareholders are protected by the law. We plan to set up a pharmacy for our business. We choose this type of business because it is one of the popular demand nowadays. Pharmacy provide variety of medicine from many products and can attract customers. Customers prefer to go to pharmacy because it is the easy way to buy medicine after clinic or hospital. This business promises more profit to the shareholders.